2021
DOI: 10.1161/str.52.suppl_1.mp57
|View full text |Cite
|
Sign up to set email alerts
|

Abstract MP57: Sex Differences in Stroke Outcome Are Associated With Constitutive Gut Dysbiosis and Stroke-Induced Gut Permeability

Abstract: Sex differences in experimental stroke are well documented, such that adult males show worse outcomes compared to adult females, including greater infarct volume, increased stroke-induced mortality and more severe sensory-motor impairment. Based on recent evidence that gut dysbiosis may be an early response to stroke, the present study tested the hypothesis that in the acute phase, stroke will result in greater gut dysbiosis and greater permeability of the gut blood barrier in males as compared to females. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the most extreme cases of ischemic stroke, this injury can result in multi-system organ failure, including acute lung injury, liver failure, and kidney failure [ 31 ]. Previous studies from our lab have shown that stroke has a profound sex-specific impact on gut architecture (implicating sex hormones as a regulator of this phenomenon) [ 32 ] and that repairing the gut is capable of robustly improving stroke outcomes [ 33 ]. Other studies have shown that the gut traffics immune cells to the brain post-stroke [ 28 ] and that dysbiosis prohibits effector T cells from traveling to the meninges post-stroke [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the most extreme cases of ischemic stroke, this injury can result in multi-system organ failure, including acute lung injury, liver failure, and kidney failure [ 31 ]. Previous studies from our lab have shown that stroke has a profound sex-specific impact on gut architecture (implicating sex hormones as a regulator of this phenomenon) [ 32 ] and that repairing the gut is capable of robustly improving stroke outcomes [ 33 ]. Other studies have shown that the gut traffics immune cells to the brain post-stroke [ 28 ] and that dysbiosis prohibits effector T cells from traveling to the meninges post-stroke [ 30 ].…”
Section: Discussionmentioning
confidence: 99%